2022
DOI: 10.14218/erhm.2021.00074
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to High-sensitivity Cardiac Troponin T Levels in Pre-dialysis Chronic Kidney Disease Patients

Abstract: Background and objectives: Cardiac troponin T (cTnT) is independently associated with cardiovascular complications in patients with chronic kidney disease (CKD). The present study aimed to determine the factors related to cTnT levels in pre-dialysis CKD patients, which result to increased cardiovascular risk.Methods: A total of 147 patients, with a mean age of 69.1 ± 14.7 years old, were enrolled. These participants were classified to estimated glomerular filtration rate (eGFR) and albuminuria categories, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Diabetes, hypertension, previous history of coronary artery disease, and cerebrovascular accident were found in this study to be associated with elevated concentrations of h-cTnT, which have been reported by other studies [24,43,44]. Findings of higher serum h-cTnT in diabetic HD patients are consistent with previous data from HD patients reported by others [36].…”
Section: Plos Onesupporting
confidence: 92%
“…Diabetes, hypertension, previous history of coronary artery disease, and cerebrovascular accident were found in this study to be associated with elevated concentrations of h-cTnT, which have been reported by other studies [24,43,44]. Findings of higher serum h-cTnT in diabetic HD patients are consistent with previous data from HD patients reported by others [36].…”
Section: Plos Onesupporting
confidence: 92%